A Bibliometric Analysis of Islamic Branding and the Political Economy of Streaming Services: A Decade of Scholarly Discourse 2013-2023 - Aprinto Aprinto; Surohim Surohim; Fransiskus Novrianto Pakpahan (Tinta Emas Institute, 2023)
The convergence of the global OTT streaming revolution and the maturation of the Islamic economy presents a critical juncture for media studies. This research employs a comprehensive bibliometric analysis to map the scholarly discourse from 2013 to 2023 at the nexus of Islamic branding, the political economy of streaming platforms, and their interplay in key Muslim-majority nations: Indonesia, Pakistan, Saudi Arabia, Iran, and the UAE. The analysis, utilizing co-citation and bibliographic coupling, reveals a robust and evolving field. Co-citation analysis identified foundational intellectual clusters centering on the Halal industry ecosystem, Muslim consumer behavior theory, and the impact of brand equity. Concurrently, bibliographic coupling illuminated contemporary research fronts, including integrated models of purchase intention in the Indonesian consumer goods sector, comparative studies of consumer hesitation and adoption, and the mediating roles of trust and brand equity in digital and Sharia-compliant markets. The study synthesizes these findings to provide a data-driven overview of the field's intellectual structure, tracing its thematic evolution and highlighting the complex negotiation between global platform logic and local religious identities. Ultimately, this bibliometric mapping not only delineates the current state of knowledge but also identifies under-explored areas, thereby offering a foundational reference and a clear agenda for future research into the co-constitution of digital capitalism and Islamic identity in the modern media ecosystem.